Plasma cell myeloma: Pendekatan diagnosis dari aspek kliniko-morfologik dan imunofenotipe - Angelina, Aina; Retnani, Diah (Jurnal Klinik dan Riset Kesehatan, 2023)
Plasma cell myeloma (PCM)/Mutiple myeloma (MM) is hematologic malignancy characterized by the proliferation of neoplastic plasma cells of bone marrow. The manifestation of disease include multifocal lytic bone lesions, increased serum or urine M protein, target organ damage, and can present as an extramedullary mass. Extramedullary tumor mass biopsy can show morphology that overlaps with other plasma cell neoplasms or malignant lymphoma, this become a diagnostic challenge especially if the clinical and radiological information is incomplete. End-organ damage attributable to abnormal plasma cell proliferation is known as CRAB consist of hypercalcemia, renal insufficiency, anemia and bone lesions. The clinical spectrum often varies so the diagnosis of PCM requires the integration of clinical, laboratory, imaging, morphology, and immunophenotype data. Histopathological examination of bone marrow biopsy and tumor mass biopsy needs to be confirmed by immunohistochemical examination and clonality tests to establish an accurate diagnosis. This review intends to explain the clinical, morphological and immunophenotypic aspects as well as construct an approach to the diagnosis of PCM.